Multiple Stimuli-Responsive Conformational Exchanges of Biphen[3]arene Macrocycle - Wang, Yiliang; Yang, Liu-Pan; Zhao, Xiang; Cui, Lei; Li, Jian; Jia, Xueshun; Fang, Jianhui; Li, Chunju (Molecules (Basel, Switzerland), 2020)
Conformational exchanges of synthetic macrocyclic acceptors are rather fast, which is rarely studied in the absence of guests. Here, we report multiple stimuli-responsive conformational exchanges between two preexisting conformations of 2,2′,4,4′-tetramethoxyl biphen[3]arene (MeBP3) macrocycle. Structures of these two conformations are both observed in solid state, and characterized by 1H NMR, 13C NMR and 2D NMR in solution. In particular, conformational exchanges can respond to solvents, temperatures, guest binding and acid/base addition. The current system may have a role to play in the construction of molecular switches and other stimuli-responsive systems.